STRATEGIC FINANCIAL MANAGEMENT IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Wirawan Widjanarko; Rachmat Pramukty; Hadita, Hadita; Yulianah, Yulianah (Jurnal Ekonomi, 2022)
Strategic planning impacts a company's finances, as does good management, but when the two strategies are synchronized, tools are available to achieve growth and development. Financial management as a tool that helps to have clear information and the real state of the company, on the other hand, strategic planning for setting goals, meeting goals and making good decisions. Financial management in Micro, Small and Medium Enterprises or better known as MSMEs which is characterized by bankruptcy and low liquidity, as a result of ineffective financial policies implemented by the owners-and motivated by a lack of knowledge about proper management of their resources. Another aspect analyzed in relation to SMEs is the absence of a homogeneous definition at the international level. This study finds differences in the financial management of MSMEs, because this is influenced by the goals of MSME actors in the company, so that it has a significant effect on competitiveness and sustainability in the market..